The effect of dried powdered leaves of castor bean Ricinus communis L. in tomato growth and its role in decreasing the infection of Orobanche ramosa L. on tomato Lycopersicum esculentum L. in green house - طباش, سمير; حداد, دينا; حبق, حنان; حوش, ماري (Latakia University Journal -Biological Sciences Series, 2022)
The effect of dried leaves powder mixed with soil in concentrations 1,2,4% of Ricinus communis on both tomato growth and parasite weed Orobanche ramosa L. germination and growth on tomato Lycopersicum esculentum L was studied, results showed the efficacy of R. communis with 2,4% concentrations in decreasing the average of germination ,tuber number and biomass of O.ramosa which were 24.20, 6.20 tuber/ plant respectively compared to infected control 63.40 tuber/plant for tuber number and 3.33, 0.17g respectively compared to infected control 5.01g for the average of orobanche dried weight with preventing the orobanche plants growth completely with 4% concentration. On the other hand using dried leaves powder of Ricinus communis mixed with soil in concentrations 2% increased non infected tomato root length which was 42.60cm compared to non- infected control 34.80 and increased non infected tomato leaf number which was 35.00 leaf/plant compared to non- infected control 30.40 leaf/plant. Thus we found the efficiency of Ricinus communis L. as an effective herbicide on Orobanche ramosa L. and safe for tomato Lycopersicum esculentum L.